2010
DOI: 10.5395/jkacd.2010.35.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture on sealing ability of root canal filling with different types of sealer through the glucose penetration model

Abstract: Objectives: To compared the effect of different levels of moisture of root canal on the sealing ability after filling with four different types of sealer. Materials and Methods: Single-rooted teeth (n = 90) instrumented to and apical size of 0.06 / 45 were randomly assigned to 12 experimental groups (n = 7 per group), positive/negative control groups (n = 3 per group). The teeth of the experimental groups (a. DRY; b. PAPER POINT DRY; c. WET) were obturated with sealer (Group 1-3: Sealapex; Group 4-6: AH plus; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“… 15 Further microleakage has been found to be least in the case of resin based sealers. 16 Cho et al have also mentioned in their study that the bond strength of final restoration was the least affected in case of resin based sealers than the zinc oxide euginol root canal sealer. 17 Kim et al have stated that resin based sealers (AH 26, EZ fill and AD Seal) are more biocompatible and have advantage in terms of radiopacity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 15 Further microleakage has been found to be least in the case of resin based sealers. 16 Cho et al have also mentioned in their study that the bond strength of final restoration was the least affected in case of resin based sealers than the zinc oxide euginol root canal sealer. 17 Kim et al have stated that resin based sealers (AH 26, EZ fill and AD Seal) are more biocompatible and have advantage in terms of radiopacity.…”
Section: Discussionmentioning
confidence: 90%
“…Mamootil et al have stated that resin-based sealers have deeper and more consistent penetration into dentinal tubules than other sealers both in vitro and in vivo 15. Further microleakage has been found to be least in the case of resin based sealers 16. Cho et al have also mentioned in their study that the bond strength of final restoration was the least affected in case of resin based sealers than the zinc oxide euginol root canal sealer 17.…”
Section: Discussionmentioning
confidence: 98%
“…The results of tests conducted in both damp and dry environments showed that the AD Seal sealer had the lowest micro-leakage and that the kind of moisture (5.25% hypochlorite or blood) had no discernible impact on the rate of sealer micro-leakage [19]. Jinah et al's [19] research showed that the type of sealer employed and the moisture level of the root canals at the time of obturation had a big impact on leakage and sealing ability. Therefore, drying procedures according to sealer types are a crucial stage in endodontic treatment and shouldn't be skipped [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some other researchers such as Jang et al (31) and Goldman et al (5) suggested totally dried root canals before the obturation process because they believed it may increase the adherence of the filling material to the dentin walls of the canal.…”
Section: Discussionmentioning
confidence: 99%